2005
DOI: 10.1523/jneurosci.0046-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Common Input across Motor Nuclei Mediating Precision Grip in Humans

Abstract: Short-term synchrony was measured for pairs of motor units located within and across muscles activated during a task that mimicked precision grip in the dominant and nondominant hands of human subjects. Surprisingly, synchrony for pairs of motor units residing in separate muscles (flexor pollicis longus, a thumb muscle, and flexor digitorum profundus, an index-finger muscle) was just as large as that for pairs of units both within the thumb muscle. Furthermore, the high level of synchrony seen across muscles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 35 publications
3
54
2
Order By: Relevance
“…Muscle-pair differences in the strength of motor-unit synchrony have also been reported by a recent study by Hockensmith et al (2005). These authors found stronger synchrony across motor units from FPL-FDP2 compared with FPL-FDP3 during a force production task that mimicked two-digit grasping (Hockensmith et al 2005).…”
Section: Heterogeneous Organization Of Common Input To Hand Musclessupporting
confidence: 66%
See 1 more Smart Citation
“…Muscle-pair differences in the strength of motor-unit synchrony have also been reported by a recent study by Hockensmith et al (2005). These authors found stronger synchrony across motor units from FPL-FDP2 compared with FPL-FDP3 during a force production task that mimicked two-digit grasping (Hockensmith et al 2005).…”
Section: Heterogeneous Organization Of Common Input To Hand Musclessupporting
confidence: 66%
“…Similarly, no visual feedback of the forces exerted on the device was given to allow a natural distribution and fluctuation of individual digit forces during object hold in response to a more natural constraint, i.e., to prevent object slip against gravity. This is a novel feature of our experimental design as the majority of previous studies examining motor-unit activity of hand muscles required subjects to generate forces against fixed force transducers with thumb and index finger under visual or auditory feedback (e.g., Hockensmith et al 2005;Huesler et al 2000).…”
Section: Force and Emg Recordingmentioning
confidence: 99%
“…Nevertheless, movements of the thumb were not completely independent from the fingers. Neural interactions involving drive to the long flexors of the fingers and thumb have been reported (Hockensmith et al 2005;Kilbreath and Gandevia 1994;Yu et al 2007). During a pressing task with the fingers and thumb, Olafsdottir et al (2005) reported that the degree of thumb enslavement depended on its position.…”
Section: Single-digit Performancementioning
confidence: 99%
“…They include the divergence of corticospinal axons to reach more than one motoneuron pool (e.g., Cheney 1978, 1980;Shinoda et al 1981; for review, see Lemon 2008) and the major overlapping and intermingling of cortical output zones to individual upper limb muscles documented in nonhuman primates (e.g., Landgren et al 1962;Rathelot and Strick 2006;Schieber and Hibbard 1993). As a result of such factors, there is short-term synchronization of motor unit discharge of functionally linked hand muscles or across muscle compartments of the multitendoned extrinsic hand muscles (Hockensmith et al 2005;Johnston et al 2005;Nordstrom et al 1992;Reilly et al 2004;Santello and Fuglevand 2004;Winges and Santello 2004). There is also evidence for coherence between cortical activity and forearm EMG (e.g., Baker et al 1997;Brown 2000;Conway et al 1995;Gross et al 2000;Salenius and Hari 2003) and coherent forces across different digits during voluntary tasks (e.g., Kilbreath et al 2002;Li 2002;Rearick and Santello 2002;Santello and Soechting 2000;Yu et al 2007).…”
Section: Mechanisms Of Force Enslavement and Force Deficitmentioning
confidence: 99%
“…Dozens of reports have since adopted this notion, including the following, among others: 1) within the same muscle (Garland and Miles 1997;Kamen and Roy 2000;Keen et al 2012;Laine and Bailey 2011;Mellor and Hodges 2005;Nordstrom et al 1990;Schmied et al 1993); 2) across synergistic muscles (Barry et al 2009;Bremner et al 1991a, b;Carr et al 1994;Gibbs et al 1997;Keen and Fuglevand 2004;McIsaac and Fuglevand 2007;Powers et al 1989;Winges and Santello 2004); 3) during tremor (Halliday et al 1999;Logigian et al 1988;Semmler and Nordstrom 1995); 4) in various neuromuscular pathologies (Baker et al 1992;Farmer et al 1990Farmer et al , 1993Kirkwood et al 1984;Mottram et al 2010;Schmied et al 1999); 5) during various muscle contraction paradigms, such as precision grip tasks (Hockensmith et al 2005;Huesler et al 2000;Kilner et al 2002;Santello and Fuglevand 2004;Winges et al 2006); 6) in exercise training (Boonstra et al 2009;Dartnall et al 2008Dartnall et al , 2011Griffin et al 2009;Mochizuki et al 2005;Schmied and Descarreaux 2010); and 7) during muscle fatigue (Boonstra et al 2008;Grönlund et al 2009;…”
mentioning
confidence: 99%